Capital Markets and External Current Accounts : What to Expect From the Euro - Decressin, Jorg (IMF Working Papers; Working Paper, 2000)
The paper compares the degree of capital market integration across euro-area countries with that across regions in Italy and provinces in Canada. Analyzing saving-investment correlations, and developing as well as fitting to the data a model of capital flows, reveal no compelling differences between the integration across countries before monetary union and that across the regions or provinces. The evidence does not suggest that EMU will prompt a major reallocation of net capital flows within the euro area that would entail sizable shifts in countries' equilibrium current accounts.